STABILIZATION OF THE HORSE MANURE THROUGH AN AEROBIC PROCESS SIMILAR TO COMPOSTING - Tellez Monzón, Lena A. (2019)
In the present study, the stabilization of horse manure (mixture of rice husk, manure and horse urine) was evaluated through an aerobic process similar to composting. The stabilization process was evaluated in two piles of horse manure for 16 weeks, taking samples every week. A decrease in temperature from 66,7 to 41,0 °C, the reduction of the density from 394,0 to 370,4 kg/m3, the reduction of the water retention capacity from 220,7 to 125,6% and the reduction of the respiratory activity of 9.8 to less than 2 mgO2/g ms/d, were indicators of the stabilization of the horse manure, the easily degradable material of manure and urine were removed by aerobic degradation and washed with irrigation, leaving only the rice husk with a minimum fraction of other materials. On the other hand, the increase in total nitrogen and a decrease in the C/N ratio at the end of the week 16 were indicative of the nitrogen fixation by microorganisms adhered to the rice husk. The stabilization and the fixation of microorganisms in the residual material of the horse manure, make this material a good support for the degradation of easily biodegradable organic material.